2005
DOI: 10.1889/1.2036286
|View full text |Cite
|
Sign up to set email alerts
|

45.2: Electro-Optics of Liquid Crystals Doped with Ferroelectric Nano-Powder

Abstract: Suspensions of ferroelectric nanoparticles in a nematic liquidcrystal host possess enhanced dielectric anisotropy, and are sensitive to the sign of an applied electric field. Here we also show that the particles contribute to the total achievable phase shift of the composite material. This approach may be used to design new materials for displays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Recently, we have shown that even at low concentrations (c part 1%), LC colloids differ strongly from the pure host material [7,8,9,10]. These colloids consist of submicron ferroelectric particles suspended in the LC host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that even at low concentrations (c part 1%), LC colloids differ strongly from the pure host material [7,8,9,10]. These colloids consist of submicron ferroelectric particles suspended in the LC host.…”
Section: Introductionmentioning
confidence: 99%
“…In such systems aggregated particles produce director distortions extending over macroscopic scales. These suspensions scatter light strongly, and possess unique structural, mechanical, electro-and magneto-optical properties [5,6].Recently, we have shown that even at low concentrations (c part 1%), LC colloids differ strongly from the pure host material [7,8,9,10]. These colloids consist of submicron ferroelectric particles suspended in the LC host.…”
mentioning
confidence: 99%
“…The discovery by Bachmann and Barner [14] that doping very fine dielectric particles into an isotropic liquid resulted in the enhancement of its sensitivity to electric fields heralded studies on the doping of ferroelectric nanoparticles (BaTiO 3 , Sn 2 P 2 S 6 ) into nematic liquid crystals [15,16]. In the beginning, the doping of nanoparticles was restricted to nematic liquid crystals due to their widespread applications and mature developments, as well as their relatively simple liquid crystal structure, which means that the doping of nanoparticles is less likely to destroy the alignment of the liquid crystal molecules.…”
Section: Introductionmentioning
confidence: 99%
“…displays, high contrast, large view angle and less backlight scattering [9][10][11] .In this communication, we are presenting the effect of metal oxide (zinc oxide) nanoparticles on the molecular alignment, thermal properties and crystallinity of 4-Cyano-4'-Pentylbiphenyl Mesogen (5CB), which is a well-known room temperature nematic liquid crystal. Experimental data have been obtained using a polarizing optical microscope, X-ray diffraction and Image analysis by MATLAB software.…”
Section: Introductionmentioning
confidence: 99%